(untitled) (قضايا سياسية, 2024)
Ukraine occupies a sensitive position of great importance in the Russian and American perception, as it is the largest dividing country between Russia and the Western alliance ، The West aspires to include Ukraine in European integration and partnership processes to reduce Russia’s influence and tighten control over it, at the same time that Russia opposes the West’s influence reaching its immediate neighbourhood ، It cannot leave Ukraine to become part of the Western security and economic system, as it considers Ukraine a region of interests and a strategic fortress that isolates it from the West . Studying the motives motivating the Ukrainian war requires discussing the characteristics and characteristics that characterize Ukraine, as well as the broader framework of its position in Russian and American strategic visions ، By clarifying Ukraine's strategic importance to Russia and the United States and their respective positions on the Ukrainian war.